A History of the University of Santo Tomas : four centuries of higher education in the Philippines (1611-2011) : volume 2 - Villarroel, Fidel (Espana Manila, Philippines : UST Publishing House, 2012)
St. Thomas Aquinas once wrote that you cannot love that which you do not know. I hope many Thomasians can have a copy of this precious work of Fr. Villarroel. Some people would describe it as a masterpiece, an epic work, a scholarly treatise, a work of a lifetime. But I prefer to call it a work of love. He wrote it for one simple reason: he loves UST. And because he loves it, he envisions this book not as a flickering candle, but a torch, inflaming the heart of every Thomasian to pursue greatness: greatness in purpose and achievement$1 (Bfor the self, the university, the country, and God.s
Part Three. Age of reforms and revolutions the nineteenth century -- Part Four. Under the American flag and the Philippine republic in the twentieth century.
Includes bibliographical references and index.
Keywords: UNIVERSITY OF SANTO TOMAS -- HISTORY